The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/jof3020019
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Susceptibility Testing of Fusarium: A Practical Approach

Abstract: In vitro susceptibility testing of Fusarium is becoming increasingly important because of frequency and diversity of infections and because resistance profiles are species-specific. Reference methods for antifungal susceptibility testing (AFST) are those of Clinical and Laboratory Standards Institute (CLSI) and European Committee on Antimicrobial Susceptibility (EUCAST), but breakpoints (BPs) have not yet been established. One of the problems is that phylogenetic distances between Fusarium species are much sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 61 publications
1
43
0
1
Order By: Relevance
“…The echinocandins and azoles had no activity; the only antifungal compound with low MICs against some strains was amphotericin B. Other authors have reported different patterns according to the species complexes; thus, Fusarium solani isolates are usually resistant to azoles and show higher MICs of amphotericin B than other species, whereas Fusarium oxysporum and Fusarium verticillioides can be susceptible to voriconazole and posaconazole (35). In our study, most isolates (9 out of 13) were identified as Fusarium proliferatum (Fusarium fujikuroi complex); a study analyzing 81 strains of the Fusarium fujikuroi complex found that amphotericin B was the most active drug, followed by voriconazole, posaconazole, isavuconazole, and natamycin, while fluconazole, itraconazole, and micafungin showed poor activity (36).…”
Section: Discussionmentioning
confidence: 94%
“…The echinocandins and azoles had no activity; the only antifungal compound with low MICs against some strains was amphotericin B. Other authors have reported different patterns according to the species complexes; thus, Fusarium solani isolates are usually resistant to azoles and show higher MICs of amphotericin B than other species, whereas Fusarium oxysporum and Fusarium verticillioides can be susceptible to voriconazole and posaconazole (35). In our study, most isolates (9 out of 13) were identified as Fusarium proliferatum (Fusarium fujikuroi complex); a study analyzing 81 strains of the Fusarium fujikuroi complex found that amphotericin B was the most active drug, followed by voriconazole, posaconazole, isavuconazole, and natamycin, while fluconazole, itraconazole, and micafungin showed poor activity (36).…”
Section: Discussionmentioning
confidence: 94%
“…Novel identification tools, such as MALDI-TOF MS, or nonculture diagnostic assays, enable both accurate and fast identification of Fusarium species in the clinical laboratory: further insight into antifungal susceptibility profiles associated with each species should help to choose an adequate first-line antifungal treatment and thus improve the prognosis of invasive fusariosis patients [93]. Susceptibility testing of clinical isolates is highly recommended in the clinical setting, not only because there are significant strain-and species-specific differences in antifungal susceptibility, but also for epidemiological studies to detect emergence of resistant strains [94]. Further data from animal models and clinical trials evaluating the optimal treatment strategy against Fusarium infections are needed to refine and improve treatment guidelines, which are currently based on data from relatively large, but uncontrolled case series.…”
Section: Deep Infectionsmentioning
confidence: 99%
“…Antifungal susceptibility testing of Fusarium spp. is now recommended in patient care [88]. The comparisons of Etest results for Fusarium spp.…”
Section: Mucoralesmentioning
confidence: 99%